PENERAPAN NILAI NASIONALISME DALAM PEMBELAJARAN PPKn TERHADAP SISWA M A AL FATTAHIYYAH SEBAGAI WUJUD PENGAMALAN SILA KE-3 PANCASILA - Shodiq, Ali Fajar; Dirgantoro, Ajar; Purnamasari, Nurna Listya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The cultivation of nationalism among students has become increasingly important amid the rapid advancement of globalization and digital technology, which has influenced the attitudes and behavior of younger generations. Civic Education (PPKn) plays a strategic role in strengthening students' national identity and fostering the values embodied in the third principle of Pancasila, namely the Unity of Indonesia. This study aimed to examine how nationalism values are implemented through Civic Education learning at MA Al Fattahiyyah and to identify the factors influencing their implementation. A descriptive qualitative approach was employed, with data collected through observations, interviews, and documentation. The collected data were analyzed using the stages of data reduction, data display, and conclusion drawing. The findings indicate that nationalism values are integrated into classroom instruction, teachers' role modeling, school routines, flag ceremonies, and other school cultural activities. These practices contribute to the development of students' patriotism, discipline, responsibility, mutual respect, cooperation, and appreciation of diversity. Nevertheless, the implementation is still challenged by the influence of globalization, the excessive use of social media, limited parental supervision, and varying levels of students' awareness. Therefore, collaboration among schools, families, and the wider community is essential to strengthen the internalization of nationalism values and promote the practical implementation of the third principle of Pancasila in students' daily lives.